Developing a student development index: an evidence from Malaysia - Abdullah, Zulhamri; Tai, Lit Cheng; Sheikh Sagoff, Syed Agil (Global Institute for Research & Education, 2014)
The study aims to develop a measure on students development in the higher educational institutions. The conceptual framework of student development is based on Bandura’s self-efficacy and Chickering’s seven vectors. Thus, this study focuses on students’ identity development, primarily on seven vectors of development, which are to develop competence, emotions, interdependence, and maturity in interpersonal relationship, self-identity, purpose, and integrity. A quantitative survey approach is employed in this study among university students in the Klang Valley, Malaysia. 479 usable responses are valid to be analysed. The sampling frame is from university’s database provided by the Academic Department 2013. The findings shows there are positive relationships between self-efficacy and Chickering’s seven vectors. Self-efficacy is also positively correlated with student satisfaction and institutional image. This study contributes to both of theoretical and practical implications on the university’s student development.